PENGARUH VARIASI PENAMBAHAN BUBUK CAMPHOR KE DALAM BAHAN BAKAR PERTALITE DAN PEMAKAIAN BUSI IRIDIUM TERHADAP TORSI DAN DAYA SEPEDA MOTOR YAMAHA VIXION - Dharmawan Adi Saputro; Ranto Ranto; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The purpose of this study were: (1) to know the effect of adding various variations of camphor powder in pertalite to the moment of torque and power of the 2010 Yamaha Vixion, (2) to determine the effect of using iridium spark plugs on the torque moment and power of the 2010 Yamaha Vixion; and (3) investigate the effect of adding various variations of camphor powder in pertalite and the use of irridium spark plugs to the torque moment and power of the Yamaha Vixion 2010. This study uses a Yamaha Vixion 2010 motorbike with police number AD 2057 BO, and framework number MH33C1005CK959299 This study uses an experimental method design. These data are analyzed by descriptive statistics which means describing the data collected only in the way it is. The results of the study are as follows: (1) There is the effect of adding various camphor powder to pertalite fuel on increasing maximum torque and power in a combination of 1 gram / liter pertalite and camphor powder, (2) There is the effect of using torque and power iridium spark plugs lower than using standard plugs, (3) There is the effect of adding various camphor powder in pertalite fuel and iridium plugs used are a decrease in torque and power in all treatments.